MiR‐21‐5p promotes cell proliferation and G1/S transition in melanoma by targeting CDKN2C. Issue 5 (24th March 2020) - Yang, Zhaohui; Liao, Bo; Xiang, Xiaoyan; Ke, Sha
Abstract : Human melanoma is a highly malignant tumor originating from cutaneous melanocytes. The noncoding RNA microRNA (miR)‐21‐5p has been reported to be expressed at high levels in malignant melanocytic skin tissues, but its potential functional role in melanoma remains poorly understood. Here, we explored the cellular effects of miR‐21‐5p on melanoma in vitro and the underlying mechanisms. Quantitative real‐time PCR was used to show that miR‐21‐5p is significantly up‐regulated in clinical samples from patients with melanoma as compared with adjacent noncancerous tissues. Overexpression of miR‐21‐5p significantly enhanced, whereas knockdown attenuated, cell proliferation and G1/S transition in melanoma cell lines (A375 and M14). Luciferase reporter assays were used to show that the cyclin‐dependent kinase inhibitor 2C ( CDKN2C ) is a downstream target of miR‐21‐5p. Furthermore, miR‐21‐5p mimics resulted in a decrease in CDKN2C expression, and CDKN2C expression was observed to be inversely correlated with miR‐21‐5p expression in melanoma tissues. Rescue experiments were performed to show that overexpression of CDKN2C partially reversed the effects of miR‐21‐5p up‐regulation on A375 cells. Consistently, knockdown of CDKN2C abolished the effects of miR‐21‐5p down‐regulation on A375 cells. Overall, our studies demonstrate that miR‐21‐5p can promote the growth of melanoma cells by targeting CDKN2C, which may induce G0/G1 phase arrest of melanoma cells. Abstract : miR‐21‐5p down‐regulates CDKN2C expression, thereby promoting G1/S transition and enhancing cell proliferation in melanoma.